Non-adaptive cognitive emotion regulation mediates the relationship between disease uncertainty and acute stress disorder in patients with ischaemic stroke - Zhou, Yanan; Zhou, Yani (Frontiers in Psychiatry, 2024)
Hospitalized patients, especially those with cerebrovascular disease, were identified as a vulnerable group suffering from acute stress disorder (ASD) and consequent psychological distress. For stroke patients, not only will they suffer from physical illness, but the uncertainty of illness caused by sudden illness may also cause patients to experience different degrees of ASD. Impact of ASD on individuals may vary according to age, gender, disease characteristics, individual personality, treatment methods, income level, family support, cognitive psychology and other factors. However, non-adaptive cognitive emotion regulation plays a crucial role in influencing individual psychological states. Therefore, we focus on exploring the predictive effects of general demographic and disease-related characteristics, maladaptive cognitive emotion regulation, and illness uncertainty on ASD after stroke, and make hypotheses. When a disease acts on the body, the patient will have the corresponding cognition of the disease, and ASD will appear at the same time. Then the maladaptive cognitive emotion regulation as an important mediating variable can aggravate the level of acute stress disorder and be verified. We used a cross-sectional design to investigate the distribution of a disease or health condition and its related factors in a specific population at a specific time. A total of 256 patients with ischemic stroke were enrolled. All patients completed a self-report questionnaire that included demographic information, illness uncertainty, cognitive emotion regulation, and ASD. The majority of hospitalized stroke patients (67.6%) developed ASD due to the COVID-19 pandemic and were therefore at risk for PTSD. More than one third (39.1%) of stroke survivors also suffered from severe psychological distress. More specifically, younger stroke patients are more likely to experience ASD than older patients. Although higher illness uncertainty scores indicate more severe ASD, adaptive cognitive emotion regulation was a protective factor. Given that individuals with ASD are susceptible to PTSD, it is critical to follow up hospitalized patients with stroke for screening for PTSD and referral to appropriate psychological services. Maladaptive cognitive emotion regulation can increase the impact of uncertainty on the traumatic experience of stroke patients. Therefore, health care institutions should increase their efforts to provide psychosocial support services to hospitalized patients.